Appropriate use of serum troponin testing in general practice: a narrative review. Issue 2 (18th July 2016) - Aroney, Constantine N; Cullen, Louise
Summary: The troponin assay was designed to assist in diagnosis and improve risk stratification for people presenting to the emergency setting with symptoms suggestive of an acute coronary syndrome. Newly developed high sensitivity assays provide reliable detection of very low concentrations of troponin and offer earlier risk stratification of patients with possible acute coronary syndrome. Cardiac troponin testing in general practice should be limited to patients presenting with ischaemic symptoms that occurred more than 24 hours previously. If these patients have no high risk clinical features and a normal electrocardiogram (ECG), they may be assessed with a single troponin assay but should be referred urgently to hospital if the result is elevated. In patients presenting with symptoms of possible acute coronary syndrome within the preceding 24 hours, or if they otherwise have symptoms consistent with unstable angina, high risk clinical features or ECG abnormalities, a serum troponin test should not be ordered and patients should be referred immediately to an emergency department. When a single troponin assay is appropriate, the test should be labelled as urgent and systems must be in place to ensure the result is conveyed immediately to the medical practitioner, as it has prognostic implications and may require an urgent action plan.